AN AUTOPSY-BASED STUDY ON THE PATTERNS OF INJURIES OF BURN CASES IN JORHAT DISTRICT, ASSAM - LAMA, BIKKI; GUPTA, VED PRAKASH; THAKURIA, DIPANKAR (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: This autopsy-based study aimed to determine the incidence of burn-related fatalities in Jorhat District, Assam, identify associated factors, investigate injury patterns and severity, explore contributing factors, examine the relationship between injuries and cause of death, differentiate between dermo-epidermal and deep burns, investigate circumstances surrounding burn injuries, and offer recommendations for prevention and forensic investigation improvements. Methods: Data were collected from medico-legal autopsies conducted at the Mortuary of the Department of Forensic Medicine, Jorhat Medical College and Hospital, Jorhat, between May 11, 2020, and May 10, 2021. Demographic information, burn characteristics, autopsy findings, and circumstances of injuries were analyzed. Results: Out of 628 medico-legal autopsies, burn-related deaths comprised 7.32% of cases. Victims with 51–60% total body surface area burns were most common (23.91%). Burns often occurred indoors, notably in kitchens (56.52%) and bedrooms (26.08%), with a majority in closed rooms (54.35%). Synthetic (47.82%) or cotton (41.30%) clothing was prevalent, and kerosene was common in alleged suicidal cases (23.92%). Most victims died within 24 h (43.46%), primarily due to shock (52.17%), and septicemia (45.65%). Dermo-epidermal burns were prevalent (93.47%), and deaths were mainly accidental (65.21%). Histopathological analysis revealed dermis and epidermis separation (82.60%), flattened and elongated epithelial cells (73.91%), congestion (76.09%), leukocyte infiltration (73.91%), capillary dilatation (67.39%), and edema (67.39%). Conclusion: This study provides comprehensive insights into burn injury characteristics, circumstances, and consequences. Recommendations include preventive measures and improvements in forensic investigation practices related to burn injuries, offering valuable implications for health care, forensic medicine, and public awareness initiatives.